PELATIHAN PEMBUATAN PUPUK KOMPOS DARI SAMPAH ORGANIK SEBAGAI REINTERVENSI MASALAH SAMPAH DI DESA KALUKUBODO KABUPATEN TAKALAR - A. Muflihah Darwis; Syamsuar Manyullei; Muh. Iqran Al Muktadir; Crefty Ainil Haq; Atika Sari; Tasya Nurul Tasrah (JIPAM : Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Waste management is still an environmental problem that requires serious attention from the government and the community. All human activities always produce waste, one of which is organic waste from household waste. One way to minimize the negative impact of domestic organic waste is to process the waste using the composting method through community-based waste management efforts. Training on making compost is carried out as an effort to minimize the impact of organic waste on the community. This activity aims to train the community to be able to process their organic waste. This activity was carried out by visiting the residents of Kalukubodo village who were on the beach on July 1, 2022. The training on making compost was carried out by demonstrating the procedures and steps for making compost in front of the villagers who were gathering. After the training was held, the enthusiasm of the residents to procure compost increased. This is evidenced by the manufacture and use of compost in one of the houses of residents who have attended this training. So that this training activity for making compost can be said to be successful